Study of Clear Air Turbulence Related to Tropopause Folding over the Romanian Airspace - Sabina Ștefan; Bogdan Antonescu; Ana Denisa Urlea; Livius Buzdugan; Meda Daniela Andrei; Cristian Necula; Sanda Voinea (Atmosphere, 2020)
Clear air turbulence (CAT) poses a significant threat to aviation. CAT usually occurs in the lower stratosphere and the upper troposphere. It is generally associated with large scale waves, mountain waves, jet streams, upper-level fronts and tropopause folds. Aircraft can experience CAT when flying in proximity of a tropopause fold. To better understand and diagnose tropopause fold- associated CAT we selected a series of cases from among those reported by pilots between June 2017 and December 2018 in the Romanian airspace. Data on turbulence were used in conjunction with meteorological data, satellite imagery, and vertical profiles. Additionally, a set of indices as Ellrod, horizontal temperature gradient, Dutton, and Brown were computed to diagnose CAT associated with tropopause folding. These indices were also analyzed to test the physics mechanisms that may explain the occurrence of severe turbulence. Results show that out of the 420 cases announced by pilots, severe turbulence was reported in 80 cases of which 13 were associated with tropopause folding.